Management of Burn Wound in Diabetic Old Patient with Panchagavya Formulations – A Case Report - Punam Sawarkar; Damini Raut; Nandini Bhojarj; Gaurav Sawarkar (Journal of Pharmacy and Bioallied Sciences)
Burn injuries are often prevalent and among the most catastrophic injuries encountered in casualty or surgery departments, involving skin and other tissues. These injuries typically result from heat sources such as solids, liquids, or fire, while scalds arise from hot liquids, electricity, chemicals, cold, friction, or radiation. Despite varying causes, the male-female ratio of burn cases remains consistent. In India, the annual incidence of burns is estimated at six to seven million. Topical antimicrobial agents are crucial for treatment. This case study focuses on an 83-year-old woman with acute burn wounds on her right leg and abdomen, accompanied by pain, discharge, foul odor, edema, and skin discoloration. Treatment involved Panchagavya Chikitsa, utilizing local applications of Gomutra twice daily for wound cleaning and Jatyadi Ghrita twice daily for wound healing over 60 days. Additionally, 15 ml of Gomutra Arka was administered internally twice daily for 15 days. Significant improvements were observed, including complete wound healing and associated symptom resolution. The positive outcomes may be attributed to the local and systemic effects of Gomutra, Jatyadi Ghrita, and Gomutra Arka, which possess antimicrobial, antiseptic, scrapping, and wound-healing properties. The findings suggest that Panchagavya formulations effectively and safely manage burn wounds, even in geriatric patients. Jatyadi Ghrita and Gomutra demonstrated promising results without causing adverse effects in this case.